Conserving koalas: A review of the contrasting regional trends, outlooks and policy challenges. (December 2015) - McAlpine, Clive; Lunney, Daniel; Melzer, Alistair; Menkhorst, Peter; Phillips, Stephen; Phalen, David; Ellis, William; Foley, William; Baxter, Greg; de Villiers, Deidre; Kavanagh, Rodney; Adams-Hosking, Christine; et al.
Abstract: The koala ( Phascolarctos cinereus ), one of the world's most iconic faunal species, was recently listed under Australian government legislation as vulnerable in the northern states of Queensland and New South Wales and in the Australian Capital Territory, but not in the southern states of Victoria and South Australia. This review synthesises empirical evidence of regional koala population trends, their conservation outlook, and associated policy challenges. Population declines are common in the northern half of the koala's range, where habitat loss, hotter droughts, disease, dog attacks and vehicle collisions are the major threats. In contrast, some southern populations are locally overabundant and are now subject to managed declines. The koala presents the problem of managing a wide-ranging species that now primarily occurs in human-modified landscapes, some of which are rapidly urbanising or subject to large-scale agricultural and mining developments. Climate change is a major threat to both northern and southern populations. The implementation of policy to conserve remaining koala habitat and restore degraded habitat is critical to the success of koala conservation strategies, but habitat conservation alone will not resolve the issues of koala conservation. There needs to be concerted effort to reduce the incidence of dog attack and road-related mortality, disease prevalence and severity, and take into account new threats of climate change and mining. Many of the complex conservation and policy challenges identified here have broader significance for other species whose population trends, and the nature of the threatening processes, vary from region to region, and through time. Highlights: Koalas are experiencing major declines in the north, while southern populations are relatively stable or increasing. New threats are looming, such as climate change and mining, whereas the long-standing threats remain undiminished. Conservation and management policies must consider all threats and their interactions, and not just focus on one or two. Much more needs to be done to recover northern koala populations and sustainably manage southern populations.